PENGEMBANGAN MEDIA PROMOSI DENGAN PEMBUATANBROSUR BERBASIS APLIKASI CANVA DI KANVILL DAU KABUPATEN MALANG - Alfan Muktafi; Ahmad Fauzi (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
Marketing is one of the important means in the business world because the growing era requires business people to always compete in order to achieve the goals set by the company. One of the promotional media that is widely used by companies is brochures. Brochure is one of the printed promotional media used to package information in an attractive design about products or services so that it can attract consumers to make purchases. Many applications are available for free that can be used in creating brochures. Among the most popular is Canva. This application is a graphic design platform used to create graphic documents and visual content. This study aimed to analyze the measurement of promotional effectiveness by making brochures using the EPIC Model & Canva application-based brochure creation as a promotional medium at Kanvill Dau Malang Regency. The research method used was action research with research procedures in the form of planning, action, observation, and reflection. The questionnaires were distributed to the business owner, 2 marketing experts, 2 computer experts, and 10 consumers. The measurement of design effectiveness was carried out using the EPIC model method (Emphaty, Persuasion, Impact, Communication). The results of the score calculation from the questionnaires from the respondents in this study and each dimension was calculated with EPIC Model showed a score of 4.5. The results showed that the brochure design was used as a promotional medium in a very effective category. So based on the results of this study it can be concluded that brochure design is very effective and appropriate to use as a promotional media at Kanvill Dau. It is expected that the brochure can be useful as an effective promotional media and can make consumers buy home service packages at Kanvill Dau